Pengaruh Pelatihan, Dukungan Manajemen Puncak, Kejelasan Tujuan, Kemampuan Teknik Personal Pada Penggunaan Sistem Informasi Akuntansi - Santa Darmika, I Gusti Ngurah Hendra; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2018)
The use of accounting information systems in current area agencies are increasingly being carried out in order to facilitate management of sources potential areas for regional development. a successful of system implementation not only determined at the sheer mastery of the oindividual skills, but the individual user behavior and factors of system largely determine successly of the system implementation. behavioral factors consist of training, top management suppor, and clarity of purpose. This research aims to test the influence of the training, top management support, clarity of purpose, and personal skills on the effectiveness use of accounting information system in the SKPD Office at Badung Regency.This research was conducted at the Office of the Inspectorate, the Regional Secretariat, the Secretariat of DPRD, BAPPEDA, Departement, Agency, Satuan Polisi Pamong Praja, and DPRD who are in SKPD Office at Badung Regency. This method using of data collection method survey with questionnaires, technique sampling in this study using random sampling techniques based on the considerations (purposive sampling). Analytical techniques used are multiple regression. This research results showed training, top of management support, clarity of accounting objectives, and the ability of influential positive personal technique on the effectiveness of use accounting information systems.To improve effectiveness of accounting information systems used, the top management should provide SKPD support materially or morally as well to intensive training for the ranks of staff so that they are motivated and increasingly adept at utilizing systems of accounting information. Keyword s: Top of Management Support, Effectivity of Using AIS, Clarity of Purpose, Personal Technique .